Georgia's Historical Past in Georgian Folklore and works of Vakhtang Orbeliani ("Old Dmanisi", "Two Dreams") - Abashidze, Pati (BLACK SEA REGION AT THE CROSSROADS OF CIVILIZATIONS, 2025)
The report discusses the problem of relationship between the poems "Old Dmanisi" and "Ori Sizmari" by the Georgian romanticist Vakhtang Orbeliani with Georgian folklore. In these poems of the poet, a great interest is expressed in the historical past of the homeland, as well as in folk poetry, where the heroic past of our country is clearly visible; The poet longs for the lost glory of his homeland and is saddened by the current reality, which is clearly visible in the analytical poems.